ANALISIS PENERAPAN PENYUSUNAN LAPORAN ARUS KAS (PSAK NO.2) PADA PT GALA JAYA MANDIRI PONTIANAK - B51111048, Falen Setiawi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The title of this thesis is Analysis of Application Preparation of Cash Flow Statements ( PSAK No. 2 ) at PT Gala Jaya PT Mandiri Pontianak . The method used is descriptive method kualitaitf which describes the state of the object under study based on those facts and data , with data collection through interviews , questionnaires , observation and study of literature . Data analysis tool used is the cash flow statement using the direct method adapted to PSAK 2 and questionnaires . Based on the analysis that has been done , it can be deduced that the PT Gala Jaya Mandiri Pontianak in the preparation of the statement of cash flows (cash flow statement) using the indirect method (indirect method) but not perfect or not in accordance with PSAK No. 2 concerning the presentation and preparation of a cash flow statement . While in decision making at the management company PT Gala Jaya Mandiri Pontianak less effective Keywords : Direct Method Cash Flow Statement Â